THE ROLE OF BRAND TRUST IN HEALTHCARE INDUSTRY: IMPACT OF BRAND EXPERIENCE, INFLUENCER EXPERTISE, AND CULTURAL VALUES ON LOYALTY AND ADVOCACY (Journal of Medical & Health Sciences Review, 2025)
The health sector is one comprising trust and consumer loyalty; hence, understanding the factors leading to consumer engagement and advocacy in this sector is a challenge. Existential large bodies of literature focus exclusively on brand trust in consumer goods and services; however, very little research focuses on how brand trust functions within the health sector. Additionally, there is a dearth of existing literature on the contribution of cultural variables, influencer knowledge, and brand experience to fostering advocacy, loyalty, and trust in healthcare marketing. The study closes this gap by examining how influencer knowledge and brand experience affect brand trust and evaluating how individual-level collectivist ideals affect the link between brand loyalty and brand trust. The desire to understand how healthcare companies may build customer trust in a high-stakes, trust-dependent business has led to the development of this research challenge.This study was based on a quantitative approach by using snowball sampling to collect data from an audience in Karachi through a Google Form. Seven hypotheses are tested here that relate brand experience with influencer expertise, brand trust, parasocial relationships, brand loyalty, and brand advocacy. From the empirical evidence of the research study, it has been proven that brand experience and influencer expertise positively affect building brand trust. This in turn would have positive spillover effects for developing parasocial relationships, brand loyalty, and brand advocacy. Furthermore, the ILVC moderated the relationship between brand trust and brand loyalty. It, therefore, adds to the richness of cultural aspects in consumer behaviour relating to healthcare marketing. This paper contributes to the academic theoretical base by advancing a comprehensive model for building brand trust and loyalty in the healthcare sector by relating brand experience, influencer expertise, and cultural context. This study gives healthcare marketers practical advice on how to use cultural values and establish experiences that foster trust while implementing marketing strategies. This study's geographical reach is constrained because it was restricted to Karachi and the data was self-reported, which restricts how far the results can be applied. To further understand the mechanisms that foster trust across industries, future studies can broaden its scope geographically, investigate other cultural aspects, and examine how these findings might be used in other fields.